Commentary on the EMA reflection paper on the pharmaceutical development of medicines for use in the older population. Issue 4 (9th February 2022) - van Riet‐Nales, Diana A.; van den Bemt, Bart; van Bodegom, David; Cerreta, Francesca; Dooley, Brian; Eggenschwyler, Doris; Hirschlérova, Blanka; Jansen, Paul A. F.; Karapinar‐Çarkit, Fatma; Moran, Abigail; Span, Jan; Stegemann, Sven; et al.
Abstract : Older people are often affected by impaired organ and bodily functions resulting in multimorbidity and polypharmacy, turning them into the main user group of many medicines. Very often, medicines have not specifically been developed for older people, causing practical medication problems for them like limited availability of easy to swallow formulations, easy to open packaging and dosing instructions for enteral administration. In 2020, the European Medicines Agency (EMA) published a reflection paper 'Pharmaceutical development of medicines for use in the older population', which discusses how the emerging needs of an ageing European population can be addressed by medicines regulation. The paper intends to help industry to better consider the needs of older people during pharmaceutical/clinical medicines development by summarising data on the most relevant topics, providing early suggestions on how to move forward and prompting expert discussions and studies into knowledge gaps. Topics include patient acceptability, (dis)advantages of an administration route, formulation, dosage form, packaging, dosing device and user instruction. While the paper is directed at older people and the pharmaceutical industry, the reflections are also relevant to younger patients with similar disease‐related needs and of value to other stakeholders parties, e.g., healthcare professionals, academics, patients and caregivers, as the paper makes clear what can be expected from industry and where collaborative work is needed. This commentary provides an overview of the different steps in the development of the reflection paper, discusses points considered most controversial and/or subject to (multidisciplinary) expert discussions and indicates their value for real world clinical practice.